AIMS TO DIGITALISE THE CIRCULATION OF PRECIOUS METALS, PRECIOUS STONES AND THEIR PRODUCTS - O. V. Umgaeva; D. Kh. Eldeev; S. A. Umgaev (Стратегические решения и риск-менеджмент)
The need to digitalise economic sectors in today’s world is perceived as an objective reality. In the circulation of precious metals, precious stones and their products, the digitalisation process is at a fairly high level, with continuous improvement. The article analyses the progress made in achieving the goals of the implementation of the State Integrated Information System in the Sphere of Control over the Circulation of Precious Metals and Precious Stones at all stages (GIIS DMDK), which is the main project of digitalisation of the industry.